PENGGUNAAN LEMBAR KERJA SISWA UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA KELAS V SEKOLAH DASAR - Tia Sritiawati, - (2019)
ABSTRACT USE OF STUDENT WORKSHEET TO IMPROVE SKILLS OF SCIENCE PROCESS STUDENTS OF CLASS V ELEMENTARY SCHOOL By Tia Sritiawati 1504869 Science process skills (KPS) are very important skills that must be possessed by students especially in science learning. But from the observations made by researchers in class V in one elementary school in Kecamatan Cidadap, the science process skills of students in the class are relatively low, especially in the aspects of observing, interpreting, and communicating. Based on the results of observations made, learning carried out so far used traditional methods, namely lectures or students only filled in their textbooks without other learning media or other activities. For this reason, researchers conducted research through the use of student worksheets to improve students' science process skills in the class. Student Worksheets were designed to guide students in improving their observing, interpreting and communicating skills. The research method used was the Classroom Action Research (CAR) method of Kemmis & Mc. Taggart that carried out in two cycles. The instruments used in this study were observation sheets of teacher and student activities, students' science process skills, KPS observation sheets, field notes and KPS evaluation tests. Based on the results of the study using the KPS observation sheet and also the results of the test with the use of student worksheets the science process skills of students in the class increased from cycle I to cycle II both from the aspects of observing, interpreting and communicating. Keywords: student worksheets, science process skills